Intradiverticular Ampulla of Vater: Personal Experience at ERCP. (27th June 2013) - Geraci, Girolamo; Modica, Giuseppe; Sciumè, Carmelo; Sciuto, Antonio
Abstract : Introduction . Conflicting results have been reported about the true impact of intradiverticula ampulla (IA) on the technical success and complication rate of endoscopic retrograde cholangiopancreatography (ERCP). Patients . A total of 500 patients who underwent ERCP were divided into two groups according to the presence (group A, 81 patients) or absence (group B, 419 patients) of IA. Success rate, difficulty at cannulation, findings at ERCP, and procedure-related complications were retrospectively reviewed. Results . Successful cannulation was achieved in 100% of group A patients compared to 98% of group B patients ( P = ns). There was a significant difference in the type of cannulation that was routinary in group B (P < 0.05 ), while requiring guidewire in group A (P < 0.05 ). Cholangitis (P < 0.05 ), microstones (P < 0.01 ), dilated common bile duct without stones (P < 0.01 ), stone recurrence (P < 0.01 ), and transient postprocedure hyperamylasemia (P < 0.01 ) were more frequently observed in group A. There was no significant difference in complication rate between both groups. Conclusions . The finding of an IA at ERCP should not be considered a predictor for failed cannulation. IA is associated with post-ERCP transient hyperamylasemia and is a risk factor for biliary stone disease and its recurrence.